An Update on the Pathogenesis and Treatment of Chronic Recurrent Multifocal Osteomyelitis in Children. - Taddio, Andrea; Zennaro, Floriana; Pastore, Serena; Cimaz, Rolando (Paediatr Drugs, 2017)
Chronic recurrent multifocal osteomyelitis (CRMO), also known as chronic non-bacterial osteomyelitis (CNO), is a rare inflammatory disorder that primarily affects children. It is characterized by pain, local bone expansion, and radiological findings suggestive of osteomyelitis, usually at multiple sites. CRMO predominantly affects the metaphyses of long bones, but involvement of the clavicle or mandible are suggestive of the diagnosis. CRMO is a diagnosis of exclusion, and its pathogenesis remains unknown. Differential diagnosis includes infection, malignancies, benign bone tumors, metabolic disorders, and other autoinflammatory disorders. Biopsy of the bone lesion is not often required but could be necessary in unclear cases, especially for differentiation from bone neoplasia. Non-steroidal anti-inflammatory drugs (NSAIDs) are the first-line treatment. Alternative therapies have been used, including corticosteroids, methotrexate, bisphosphonates, and tumor necrosis factor (TNF)-α inhibitors. No guidelines have been established regarding diagnosis and treatment options. This manuscript gives an overview of the most recent findings on the pathogenesis of CRMO and clinical approaches for patients with the condition.
Keywords: Adrenal Cortex Hormones; Anti-Inflammatory Agents, Non-Steroidal; Child; Chronic Disease; Diagnosis, Differential; Humans; Osteomyelitis; Recurrence; Tumor Necrosis Factor-alpha